A BIZARRE PROGRESSION OF CHRONIC LYMPHOCYTIC LEUKAEMIA INTO DIFFUSE LARGE B-CELL LYMPHOMA - Danish Shakeel ,; Qadir, Hira; Mahad Mirza Baig,; Shah Mureed Ojla , (Journal of Ayub Medical College Abbottabad, 2023)
A 65-year-old male presented with complaints of weakness, lethargy, abdominal pain, and low-grade fever for the last few months. His examination revealed generalized lymphadenopathy and splenomegaly. A subsequent laboratory workup revealed atypical lymphoid cells with prominent double-bright positivity of CD19 and CD5 markers. Further investigations revealed deletion of the ATM (11q22.3) gene, and in accordance with other diagnostic factors, the patient was diagnosed with B-cell chronic lymphocytic leukaemia. Thus, treatment was initiated with oral chemotherapy followed by rituximab-bendamustine. After three weeks, he presented to the emergency room with a fever and worsening abdominal pain. On examination, massive splenomegaly was found. After stabilization, a bone marrow biopsy revealed findings which, in light of the clinical symptoms, were consistent with Richter's transformation of B-Cell chronic lymphocytic leukaemia into Diffuse large B-Cell Lymphoma